(untitled) (KYAMC Journal, 2020)
Background: Pre-eclampsia is one of the major causes of maternal and perinatal morbidity and mortality. Fetal and maternal outcomes are directly related to the duration of gestational age and severity of preeclampsia. Objective: To evaluate the fetal outcome in patients having severe pre-eclampsia following early delivery. Materials and Methods: In this observational study, a total of 100 pregnant women with severe preeclampsia were divided into two groups: Group A- delivery were done <48 hours after admission and Group Bdelivery were done >48 hours after admission. Antenatal corticosteroid were given in both groups when gestational age >28 weeks and <37 weeks. Data were recorded in a pre-designed questionnaire and analyzed by computer based software SPSS windows version 25 and results were presented in tabulated form. Statistical significance was defined as p-value <0.05 and the chi-Square test were done. Results: Out of 100 severe preeclamptic women, 66 were in group-A and 34 were in group-B. Most of the study subjects were in 20-30 years age group, The mean gestational age were 36.00± 2.456 weeks and 33.44± 2.699 weeks respectively (p<0.001). Antenatal Corticosteroid was more used in group-B (88.24%) than group-A (30.30%) which was statistically significant (p<0.001). The neonatal outcome of the study subjects where all the parameters were non-significant except IUFD and Early neonatal death that were more in group-B than group-A. IUFD (p<0.001) and Early neonatal death (p=0.011). Conclusion: The neonatal complications were less with early termination of pregnancy in severe pre-eclampsia patients. KYAMC Journal Vol. 11, No.-3, October 2020, Page 137-140